Analisis Penerapan Perhitungan Harga Pokok Produksi Dengan Metode Full Costing dan Variabel Costing Pada UMKM Rumah Jahit Akhwat Makassar - Inra Mayuputra, Andi Tenri; Sahade; S, Masnawaty (Yayasan Sagita Akademia Maju, 2024)
This research aims to analyze the application of calculating the cost of production using the full costing and variable costing methods for UMKM Rumah jahit akhwat Makassar. The population of this research is all items of finished goods produced by UMKM Rumah jahit akhwat Makassar. The sample for this research is robes produced by the UMKM Rumah jahit akhwat Makassar for the production period in 2022. Data collection was carried out using interview and documentation techniques. Data analysis was carried out using descriptive quantitative analysis techniques. The results of this research show that applying the calculation of the cost of production using the full costing method and variable costing will be more accurate in determining the cost of production even though using the full costing method will appear to have very high costs because this type of cost of production calculation includes all costs in the calculation. thus giving rise to costs which tend to be higher but are more accurate than using calculations from the company or using variable costing methods where in calculating the cost of production the costs that have been recognized in the production period are not included in the calculation of the cost of production for that period.